The Law on Liability for Reduced Property Values Caused by Planning Decisions in the Federal Republic of Germany - Gerd Schmidt-Eichstaedt (Washington University Global Studies Law Review, 2007)
There are two major questions in German law concerning injuries caused by planning decisions. First, what rights does a landowner have when private property, zoned by a binding land-use plan for a private-type land use, is subsequently designated for public purposes? Second, what rights does a landowner have when a planning authority revises a permitted private-type land-use category to a less valuable category? This Article first looks at these two main questions. It then proceeds to analyze the law regarding other types of planning decisions that may also have negative effects on property values, such as temporary moratoria.
Keywords: Regulatory takings; Just compensation (Eminent domain); Land use planning; Property rights; Real estate appraisal; Germany